ZOONOMYC LEXIS. ZOONYMS COW, BULL AND OX, THEIR ETYMOLOGY, SEMANTICS AND FUNCTION IN ENGLISH LANGUAGE - Смуглякова, Марина; Пономаренко, Наталия (SWorldJournal, 2020)
The article focuses on the semantic and functional peculiarities of the English zoonyms. The comprehensive etymology, semantic and functional analysis of the English zoonyms with the help of different methods was carried out. In-depth knowledge of phraseo